Evaluation and history: a traditional tale - Ortíz Jiménez, José Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2010)
It shows which interactions between the educative evaluations are in History and these discipline developments. It points out that the first history tests of the State Examinations were sustained in the homeland History proposal supported by the Colombian History Academy. An analysis of the tests allows grouping the questions in traditional working lines of this History version